Caloplaca cerina en los Pirineos de Huesca. - Esteve-raventós, F.; Arenal, F.; González, V.; Burgaz Moreno, Ana Rosa (Botanica Complutensis, 1999)
A. R. BtRGAz, F. ARENAL, V. CONZÁLEz AND F. ESTEvE-RAvENTóS. 1999. Caloplaca cer/na ín thc Pyrenees mountains of Huesca Province. Eot, Complutensis 23: 53-57. A population of Caloplaca cerina (Ehrh. ex t-ledwig) Th. Fr. from the subalpine belt in Huesca Province with an infrequent ascospore septum thickness is studied. Macro and microphotographs of the most striking features are added.